Juvenile Delinquency dalam Bentuk Penyalahgunaan Narkoba - Chitra Fraghini; Suci Putri (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
Adolescents are the next generation for building the nation. Therefore, the juvenile delinquency against drug abuse increasingly from time to time, become one of concern to the government. The Causes factors of drug abuse by adolescents like as the miss of parenthood, the absence of empowerment by parents, the environment, peers. Parenthood plays an important role in preventing juvenile delinquency in the form of drug abuse. Lack of religiosity and moral ethics causes the adolescents to act brutally, lack of self-control also makes adolescents so vulnerable and the end they falling into a drug abuse trap. The social environment that does not support the growth of adolescents is the other factor that makes adolescently vulnerable to falling into drug use. One effort to overcome juvenile delinquency problems against drug abuse is still being carried out by related parties. One of the efforts is eradicated its circulation. But if it is not supported by the environment, drug problems will continue to run rampant and damage the adolescents.